1998
DOI: 10.1073/pnas.95.23.13612
|View full text |Cite|
|
Sign up to set email alerts
|

Impairing follicle-stimulating hormone (FSH) signalingin vivo: Targeted disruption of the FSH receptor leads to aberrant gametogenesis and hormonal imbalance

Abstract: authors request that the following corrections be noted. It was accidentally stated that the studies by Kajita et al. (1) and Lee et al. (2) dealt with cinnamoyl-CoA reductase modified plants when in fact they concerned 4-coumarate:coenzyme A ligase (4CL) transgenic plants. Lignin concentration was reduced by down-regulation of 4CL activity in both studies (1, 2). In a subsequent article, Kajita et al. (3) reported a negligible decrease in lignin concentration and a decreased syringyl-toguaiacyl ratio for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
475
2
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(508 citation statements)
references
References 45 publications
26
475
2
5
Order By: Relevance
“…The contrast with LH-␤ mutations [12] implies that either the LH receptor itself or constitutively produced T has a role in male fetal sexual differentiation. Inactivating mutations in the FSH receptor result only in oligozoospermia with reduced testicular size and normal fertility [16], similar to the phenotypes observed in FSH-␤ and FSH-receptor knockout mice [17,18]. This finding implies that the presence of FSH is not an absolute requirement for the pubertal initiation and maintenance of spermatogenesis or fertility, a conclusion identical to that ascertained in the FSH and LH depletion experiments in man described above.…”
Section: Endocrine Regulation Of Testicular Functionsupporting
confidence: 76%
“…The contrast with LH-␤ mutations [12] implies that either the LH receptor itself or constitutively produced T has a role in male fetal sexual differentiation. Inactivating mutations in the FSH receptor result only in oligozoospermia with reduced testicular size and normal fertility [16], similar to the phenotypes observed in FSH-␤ and FSH-receptor knockout mice [17,18]. This finding implies that the presence of FSH is not an absolute requirement for the pubertal initiation and maintenance of spermatogenesis or fertility, a conclusion identical to that ascertained in the FSH and LH depletion experiments in man described above.…”
Section: Endocrine Regulation Of Testicular Functionsupporting
confidence: 76%
“…One of the most important biochemical signaling networks involved in controlling normal spermatogenesis in mammals exists between the anterior lobe of the pituitary gland and Sertoli cells in the testis (Griswold et al, 1975(Griswold et al, , 1976(Griswold et al, , 1977Orth, 1984;Singh and Handelsman, 1996;Kumar et al, 1997;Tapanainen et al, 1997;Dierich et al, 1998). The biological events controlled by this endocrine mechanism result from the interaction of follicle-stimulating hormone (FSH) with the FSH receptor and the subsequent transduction of molecular information across the membrane leading to the production of second messengers such as cAMP (Means et al, 1980) and Ca 2 + (Chaudhary et al, 1996;Lalevee et al, 1999) and changes in gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…1 Follicle stimulating hormone (FSH), through interaction with its specific receptor, FSHR, plays an essential role in mammalian reproduction and ovarian folliculogenesis. 2 Binding of FSH to FSHR results in adenylyl cyclase activation leading to cAMP synthesis, associated with intracellular rise of Ca 2ϩ , activation of protein kinase A (PKA) and other downstream signal transduction pathways. [2][3][4][5][6] It has been reported that FSH treatment stimulates cell proliferation on normal human OSE cells, immortalized OSE cells and OC cell lines.…”
mentioning
confidence: 99%
“…2 Binding of FSH to FSHR results in adenylyl cyclase activation leading to cAMP synthesis, associated with intracellular rise of Ca 2ϩ , activation of protein kinase A (PKA) and other downstream signal transduction pathways. [2][3][4][5][6] It has been reported that FSH treatment stimulates cell proliferation on normal human OSE cells, immortalized OSE cells and OC cell lines. 7,8 However, little has been known on the effects of FSH in the process of tumorigenesis and growth stimulation on human OSE at molecular levels.…”
mentioning
confidence: 99%